Topography and land cover of watersheds predicts the distribution of the environmental pathogen Mycobacterium ulcerans in aquatic insects. - Kevin Carolan; Andres Garchitorena; Gabriel E García-Peña; Aaron Morris; Jordi Landier; Arnaud Fontanet; Philippe Le Gall; Gaëtan Texier; Laurent Marsollier; Rodolphe E Gozlan; Sara Eyangoh; Danny Lo Seen; et al. (PLoS Neglected Tropical Diseases)
Background An understanding of the factors driving the distribution of pathogens is useful in preventing disease. Often we achieve this understanding at a local microhabitat scale; however the larger scale processes are often neglected. This can result in misleading inferences about the distribution of the pathogen, inhibiting our ability to manage the disease. One such disease is Buruli ulcer, an emerging neglected tropical disease afflicting many thousands in Africa, caused by the environmental pathogen Mycobacterium ulcerans. Herein, we aim to describe the larger scale landscape process describing the distribution of M. ulcerans. Methodology Following extensive sampling of the community of aquatic macroinvertebrates in Cameroon, we select the 5 dominant insect Orders, and conduct an ecological niche model to describe how the distribution of M. ulcerans positive insects changes according to land cover and topography. We then explore the generalizability of the results by testing them against an independent dataset collected in a second endemic region, French Guiana. Principal findings We find that the distribution of the bacterium in Cameroon is accurately described by the land cover and topography of the watershed, that there are notable seasonal differences in distribution, and that the Cameroon model does not predict the distribution of M. ulcerans in French Guiana. Conclusions/significance Future studies of M. ulcerans would benefit from consideration of local structure of the local stream network in future sampling, and further work is needed on the reasons for notable differences in the distribution of this species from one region to another. This work represents a first step in the identification of large-scale environmental drivers of this species, for the purposes of disease risk mapping.